Correlation between LCX-QFR and clinical outcomes following a single-stent strategy for left main bifurcation lesions - Zhang, Cheng-Duo; Zhou, Ji-Sheng; He, Li-Yun; Xu, Xin-Ye; Wang, Yu-Peng; Cui, Ming (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThe aim of this study was to investigate the quantitative flow ratio (QFR) outcomes in the left circumflex artery (LCX) following the placement of a crossover stent from the left main coronary artery (LM) to the left anterior descending artery (LAD) in LM bifurcation lesions. In addition, we sought to assess the relationship between these QFR results and clinical prognoses.BackgroundThe treatment approach for LM bifurcation lesions remains a topic of debate, with the LM-LAD single-stent technique being one possible option. QFR, a fractional flow reserve calculation method derived from angiography that does not require pressure guide wires, could serve as an alternative functional assessment of the LCX. This study aims to evaluate the clinical outcomes of postoperative LCX by utilizing QFR measurements, addressing a current gap in the relevant literature on this topic.MethodsThis study was a retrospective, single-center analysis of patients with LM bifurcation lesions who underwent percutaneous coronary intervention (PCI) guided by intravascular ultrasound. QFR values were derived from angiographies. The primary endpoint was the 1-year rate of major adverse cardiac events, defined as a composite of cardiovascular death, target bifurcation-related myocardial infarction (MI), or target bifurcation revascularization. The secondary clinical endpoint was defined as the persistence or recurrence of angina pectoris after PCI.ResultsWe analyzed 91 patients from a total of 180 who were screened for LM bifurcation lesions. All patients completed the 1-year follow-up. The pre- and post-PCI QFR values were 0.89 ± 0.09 and 0.86 ± 0.11, respectively. Subgroup analysis showed that 74 patients were in the postoperative QFR ≥0.80 group, whereas 17 patients were in the QFR <0.80 group. In addition, 32 patients had a ΔQFR ≥0, and 58 patients had a ΔQFR <0. Nine patients (9.9%) achieved the primary endpoint, including one patient with non-ST elevation myocardial infarction who received revascularization in both the LM-LAD and LCX arteries. In addition, nine patients (9.9%) reported no substantial improvement in their chest pain symptoms. Post-LCX-QFR <0.8 was associated with a higher 1-year incidence of cardiovascular death or MI (P = 0.036). ΔQFR proved to be a robust predictor of the 1-year incidence of the primary endpoint, with an incidence of 15.3% in the ΔQFR ≥0 group compared to 0% in the ΔQFR <0 group (area under the curve: 0.822; 95% CI: 0.728–0.895, P < 0.001), especially when ΔQFR ≤−0.03.ConclusionsAfter the LM-LAD single-stent strategy for LM bifurcation lesions, a ΔQFR of LCX ≤−0.03 was associated with a higher risk of 1-year main adverse cardiac events, indicating the superior prognostic value of the post-PCI physiological assessment.